1972
DOI: 10.1139/b72-322
|View full text |Cite
|
Sign up to set email alerts
|

Histology and ultrastructure of oat blue dwarf virus infected oats

Abstract: 1972. Histology and ultrastructure of oat blue dwarf virus infected oats. Can. J. Bot. 50: 2511-2519. The oat blue dwarf virus is a small spherical virus (28-30 nm) in diameter and is obligatorily transmitted by the aster leafhopper Mncrosreles fascfions StB1. The virus causes abnormalities in the phloem development of infected plants. Hyperplasia and limited hypertrophy of phloic procambium, in a given procambial strand, begin only after the maturation of the first protophloem sieve-tube element in that parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…It is interesting to point out that although the tumour-inducing plant viruses consist of diverse virus families with different genome properties and replication strategies (DNA or RNA), they are all similarly characterised with phloem-limited accumulations in their natural host plants. More importantly, they similarly induce hyperplastic development of phloem tissue 8 9 11 14 ; therefore, virus accumulation and replication of those RNA viruses in the tumour tissue need to be analysed in great detail. In this study, immunofluorescence experiments showed that RBSDV exclusively accumulates in phloem and neoplastic cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to point out that although the tumour-inducing plant viruses consist of diverse virus families with different genome properties and replication strategies (DNA or RNA), they are all similarly characterised with phloem-limited accumulations in their natural host plants. More importantly, they similarly induce hyperplastic development of phloem tissue 8 9 11 14 ; therefore, virus accumulation and replication of those RNA viruses in the tumour tissue need to be analysed in great detail. In this study, immunofluorescence experiments showed that RBSDV exclusively accumulates in phloem and neoplastic cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified by the bacterium Agrobacterium tumefaciens , which induces crown gall tumour and is the most intensively studied plant tumour-inducing agent 6 . Many plant viruses are known to induce enation, tumour or gall formations in host plants; these types of viruses belong to the Reoviridae , Luteoviridae , Geminiviridae and Tymoviridae families 7 8 9 10 11 12 13 14 15 .…”
mentioning
confidence: 99%
“…Unbound crystalline bodies have likewise been illustrated from plants infected by viruses, for example in oats infected with the blue dwarf virus (Zeyen and Banttari 1972), solely insect-transmitted, or by other pathogens (Fattah and Webster 1984;Sanger et al 1998). The 28-30 nm virus particles forming the crystalline bodies described by Zeyen and Banttari (1972) were equally numerous in phloem cells, even intermixed with degraded host tissue, and in this respect may show features analogous to those described here. However, the OPs were smaller, and not detected in cells remote from colonized tissue, occurring even in cell walls in the susceptible cv., a location where virus particles are not expected to occur.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of infections with low titers of members of the Marafivirus genus, infected tissues present almost imperceptible alterations of mitochondria and/or chloroplasts (31) or hyperplasia and hypertrophy of phloem and adjacent parenchyma cells (3,38), as seen with GAMaV and OBDV. Anatomical analyses of the bark tissues from CSD-affected trees showed, below the graft union, overproduction and degradation of phloem and collapse and necrosis of sieve tubes and companion cells, but there was no reference to mitochondria or chloroplast morphological alterations (30), which is in agreement with expectations with respect to morphological alterations for marafiviruses.…”
Section: Discussionmentioning
confidence: 99%